EFEK PEMBERIAN SEDUHAN SERBUK HERBA SELEDRI (Apium graviolens L.) TERHADAP KADAR ASAM URAT SERUM DARAH AYAM LEGHORN JANTAN HIPERURIKEMIA - Kristiyani, Ani (Media Farmasi Indonesia, 2021)
Apium graviolens L. is a medicinal plant that is useful for treating gout. Flavonoids are components of chemical compounds found in celery because they can work as antioxidants and inhibit the action of the xanthine oxidase enzyme to form uric acid. This study aims to determine the effect of giving celery herb powder on the blood serum uric acid levels of hyperuricemia male leghorn chickens. This study used twenty-five male leghorn chickens which were randomly divided into 5 groups. All groups were made hyperuricemia by being given 100% chicken liver juice 5 mL/l kg BW once a day orally during treatment. Group 1 was given 0.5% CMC suspension solution as a negative control group. Group 2 was treated with allopurinol 14 mg/1.5 kg BW in CMC 0.5% as a positive control. Groups 3, 4, 5 received infusion of celery herb powder in the order of doses (0.6 g/1.5 kg BW), (1.2 g/1.5 kg BW), (1.8 g/1.5 kg BW). Examination of uric acid levels was carried out on days 0, 4, 8, 12. The results showed that steeping celery could reduce uric acid levels in proportion to the dose. The greater the dose given, the greater the decrease in uric acid levels. The dose of celery herb group 3 (1.8 g/1.5 kg BW) was the most effective doses because it had the same value as the positive control.